Teriparatide Replacement Therapy for Hypoparathyroidism During Treatment With Lenvatinib for Advanced Thyroid Cancer: A Case Report - Porcelli, Tommaso; Sessa, Francesca; Caputo, Angela; Catalini, Christian; Salvatore, Domenico (Frontiers in Endocrinology, 2018)
Thyroid cancer metastasizes in 4% of cases. Approximately two-thirds of these patients are refractory to radioactive iodine-131 (RAI) therapy and have a poor 10-year survival prognosis. Treatment with tyrosine kinase inhibitors (TKIs) may be administered in selected RAI-refractory patients. However, these agents are often associated with adverse events, including vomiting. We report the case of a patient affected by RAI-refractory thyroid cancer with lung and intracranial metastases undergoing treatment with the antiangiogenic TKI lenvatinib, and with teriparatide replacement therapy for postsurgical hypoparathyroidism. Due to lenvatinib-related vomiting, which did not respond to therapy, conventional oral calcium supplementation failed to maintain normal serum calcium levels and the patient had repeated episodes of hypocalcemia. Subcutaneous teriparatide injections restored serum calcium levels, and thus lenvatinib therapy could be continued. This experience indicates that hormone replacement with teriparatide is a feasible option for cancer patients affected by hypoparathyroidism not treatable with oral calcium supplementation.